The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.5606/tgkdc.dergisi.2020.18605
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of hybrid and Norwood Stage I procedures for the treatment of hypoplastic left heart syndrome and its variants

Abstract: Bu çalışmada, hipoplastik sol kalp sendromu ve varyantlarının tedavisinde hibrit ve Norwood Aşama I işlemlerinin sonuçları sunuldu. Ça lış ma pla nı: Bu çalışmada Mart 2011-Ekim 2018 tarihleri arasında hipoplastik sol kalp sendromu veya varyantları nedeniyle ameliyat edilen toplam 97 pediatrik hasta retrospektif olarak değerlendirildi. Hastaların 32'sine (28 erkek, 4 kız; medyan yaş 5 gün; dağılım 1-25 gün) Norwood Aşama I ameliyatı (Grup N) yapılırken, geriye kalan 65 hastaya (44 erkek, 21 kız; medyan yaş 6 g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…Hypoplastic left heart surgery is a relatively new practice in Turkey and the results are improving with the increasing experience. 10 The relation between age and surgical mortality is well known and documented in almost all publications. Mortality and morbidity were higher in neonatal age group as expected, following infants.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hypoplastic left heart surgery is a relatively new practice in Turkey and the results are improving with the increasing experience. 10 The relation between age and surgical mortality is well known and documented in almost all publications. Mortality and morbidity were higher in neonatal age group as expected, following infants.…”
Section: Discussionmentioning
confidence: 99%
“…Hypoplastic left heart surgery is a relatively new practice in Turkey and the results are improving with the increasing experience. 10…”
Section: Discussionmentioning
confidence: 99%
“…[ 8 ] As we understand from our early experience and the reports from other institutes, the mortality and morbidity rates of clinics can be quite high, when they are in the learning curve for Norwood surgery[ 9 , 10 ] and it can be speculated that Norwood surgery is still in the development phase in our country. [ 11 - 13 ] However, early mortality after Norwood surgery still stands out as the most important problem that needs to be tackled.…”
Section: Discussionmentioning
confidence: 99%
“…[ 14 ] However short- and long-term outcomes of hybrid procedures have shown great variability including some very unfavorable results. [ 15 ] In Turkey, Erek et al[ 11 ] reported the comparison of surgical and hybrid Norwood procedures and showed that the hybrid approach did not have promising results. Discouraging results were obtained in our attempts as well, five of six patients died in the early period and one died in the inter-stage period.…”
Section: Discussionmentioning
confidence: 99%
“…It is used as a standard of care in some centers, and others use this approach in lieu of the Norwood procedure for particular indications, like severe LV outflow tract obstruction or in low-birth-weight neonates. 41,42 This technique consists of placing a band around each pulmonary artery to limit flow to the pulmonary vasculature. Additionally, a metal stent is placed on the ductus arteriosus, to maintain its patency and allow for systemic perfusion.…”
Section: Surgical Managementmentioning
confidence: 99%